Social Introspection of I. A. Bláha and Wittgenstein’s’ Argument Counter to Private Language. Anniversary Study on Introspection Approach in Social Sciences. - Janák, Dušan (Qualitative Sociology Review, 2010)
The following text discusses the method of social introspection of the Czech philosopher and sociologist I.A. Bláha. It focuses both on presenting the method and exploring its potentials and limits in order to understand social reality. The application of the Wittgenstein´s argument against the private language as a critique of the introspective perspective and a brief analysis of the phenomenological approach in sociology will help to assess the boundaries of this approach. Theoretical conclusions of application of the introspection method in sociology are drawn at the end of the text and thus allow to assess applicability of the Blaha’s own method.